واقع التنمر لدى طالبات المرحلة المتوسطة بمحافظة رماح وسبل الحد منه في ضوء التربية الإسلامية - السبيعي، ميثاء بنت فالح مذخر; العبدالكريم، فوزية بنت عبدالمحسن بن عبدالكريم (المؤسسة العربية للتربية والعلوم والآداب, 2024)
هدفت الدراسة إلى التعرف على واقع التنمر لدى طالبات المرحلة المتوسطة في محافظة رماح وبيان الأسباب والمظاهر التي تؤدى إلى مشكلة التنمر لدى طالبات المرحلة المتوسطة وأيضا تبيان سبل مواجهة ظاهرة التنمر المدرسي لدى طالبات المرحلة المتوسطة في ضوء التربية الإسلامية. ولتحقيق هدف الدراسة اعتمدت الباحثة على المنهج الوصفي التحليلي، حيث تكون مجتمع الدراسة من جميع معلمات المرحلة المتوسطة بتعليم محافظة رماح والبالغ عددهن (۹۱) معلمة، وقد قامت الباحثة بتوزيع أداة الدراسة على جميع المعلمات، استجاب منهن (۸۳) معلمة، وهو ما يمثل (91.2%) من إجمالي مجتمع الدراسة. وبتحليل استجابات أفراد الدراسة أظهرت النتائج أن واقع التنمر لدى طالبات المرحلة المتوسطة من وجهة نظر المعلمات في محافظة رماح جاء بدرجة عالية، ومن أبرز مظاهر التنمر أن الطالبة المتنمرة تتلفظ بالتعليق السلبي على مظهر وشكل زميلاتها وذلك يعد من التنمر المنتشر بين الطالبات، وكذلك أن التنمر اللفظي والتعليقات والتلميحات سواء على الشكل أو الملبس أصبح سلوك كثير من الطالبات المتنمرات على زميلاتهن. كما أظهرت نتائج الدراسة أيضا أن هناك موافقة بشدة بين أفراد الدراسة على الأسباب والعوامل الأسرية للتنمر بين طالبات المرحلة المتوسطة الأسباب والعوامل الأسرية حيث حصلت على متوسط حسابي مرتفع جدا (4.21) بينما جاءت الأسباب المدرسية في المرتبة الثانية بمتوسط حسابي 4.06. وفيما يتعلق بسبل الحد من ظاهرة التنمر في ضوء التربية الإسلامية من وجهة نظر المعلمات في محافظة رماح، أظهرت الدراسة أن هناك موافقة بشدة بين أفراد الدراسة على أن الإسلام نهى عن خداع الناس المؤدي إلى إخافتهم وترويعهم والاستهزاء بهم ولو على سبيل المزاح، وبناء على تلك النتائج توصي الباحثة بتوعية الأسرة بأهمية التوجيه السلوكي للطالبات والتأكيد على التعامل الجيد مع زميلاتهن بما يساهم في الحد من التنمر. The study aimed to identify the reality of bullying among middle school students in Ramah Governorate and to clarify the causes and manifestations that lead to the problem of bullying among middle school students and to show ways to confront the phenomenon of school bullying among middle school students in the light of Islamic education. To achieve the objective of the study، the researcher relied on the descriptive analytical approach and the study population consisted of all middle school teachers in the education of Ramah Governorate، which numbered (91) teachers، and the researcher distributed the study tool to all teachers، of whom (83) teachers responded، which represents (91.2%) of the total study population. By analyzing the responses of the study members, the results showed that the reality of bullying among middle school students from the point of view of teachers in Ramah Governorate came to a high degree, and one of the most prominent manifestations of bullying is that the bullying student utters a negative comment on the appearance and shape of her colleagues, and this is considered widespread bullying among students, as well as that verbal bullying, comments and hints, whether on form or clothing, has become the behavior of many students bullying their colleagues. The results of the study also showed that there is strong agreement among the study members on the family causes and factors of bullying among middle school students, family causes and factors, as they obtained a very high arithmetic average (4.21), while school reasons came in second place with an arithmetic average of 4.06. With regard to ways to reduce the phenomenon of bullying in the light of Islamic education from the point of view of teachers in Ramah Governorate, the study showed that there is strong agreement among the study members that Islam forbade deceiving people leading to scaring them, intimidating them and mocking them, even as a joke, and based on these results, the researcher recommends educating the family about the importance of behavioral guidance for students and emphasizing good dealing with their colleagues, which contributes to reducing bullying.
Keywords: التربية الإسلامية -- التنمر المدرسي -- السلوكيات العدوانية -- التوجه السلوكي